Bibliometric Analysis of Trends in Human Vaccine Development, Law, and Ethics - Rika Noviriza; Defia Roza; Elsa Yuniarti; Alfitri Alfitri; Fitra Arya Dwi Nugraha; Arif Paria Musta; Yulia Susanti (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: The global health crisis triggered by COVID-19 in 2020 placed unprecedented emphasis on the rapid creation and worldwide dissemination of vaccines, while also bringing ethical and legal questions to the forefront of public and academic debate. Methods: Using a bibliometric framework, this study analyzes scholarly publications addressing vaccination in relation to ethics and law over the period 1970–2024, drawing on records indexed in the Scopus database. Research productivity and collaboration patterns were assessed based on publication year, authorship, country of origin, institutional affiliation, and document type. Network visualization performed with VOSviewer revealed five dominant thematic clusters shaping the vaccine research landscape. Results: The findings demonstrate a pronounced expansion in publication volume, particularly in the post-pandemic period, with the United States emerging as the most influential contributor. Conclusion: This analysis highlights the critical role of cross-national collaboration and offers evidence-based insights to support the advancement of ethical governance, legal regulation, and public health policy in vaccination research.